1994
DOI: 10.1530/eje.0.1300125
|View full text |Cite
|
Sign up to set email alerts
|

Octreotide exerts different effects in vivo and in vitro in Cushing's disease

Abstract: The effect of the long-acting somatostatin analog octreotide (SMS 201-995) on adrenocorticotropin (ACTH) secretion was studied in five patients with untreated Cushing's disease in vivo and in six human corticotropic adenoma cell cultures in vitro. For the in vivo study, 100 micrograms of octreotide sc was given 30 and 180 min after cannulation of the cubital vein and 100 micrograms of corticotropin-releasing hormone (CRH) was injected iv at 210 min. Serum ACTH and cortisol levels were measured for 390 min. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 0 publications
1
72
0
4
Order By: Relevance
“…In contrast to GH-producing pituitary adenomas, which have a high degree of sst 2 expression, sst 2 expression by corticotroph adenomas is low (de Bruin et al 2009b). This explains why the sst 2 -targeting somatostatin analogs octreotide and lanreotide are generally ineffective in the treatment of CD (Lamberts et al 1989, Stalla et al 1994. The low sst 2 expression is thought to result from downregulating effects of high circulating cortisol levels.…”
Section: Drugs With Proven Clinical Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to GH-producing pituitary adenomas, which have a high degree of sst 2 expression, sst 2 expression by corticotroph adenomas is low (de Bruin et al 2009b). This explains why the sst 2 -targeting somatostatin analogs octreotide and lanreotide are generally ineffective in the treatment of CD (Lamberts et al 1989, Stalla et al 1994. The low sst 2 expression is thought to result from downregulating effects of high circulating cortisol levels.…”
Section: Drugs With Proven Clinical Efficacymentioning
confidence: 99%
“…The low sst 2 expression is thought to result from downregulating effects of high circulating cortisol levels. Indeed, several in vitro studies suggested that exposure to glucocorticoids diminishes sst 2 expression both in GH-and ACTH-secreting cell lines (Schonbrunn 1982, Stalla et al 1994, Xu et al 1995, Park et al 2003, de Bruin et al 2009a.…”
Section: Drugs With Proven Clinical Efficacymentioning
confidence: 99%
“…However, subsequent studies in Nelson's syndrome have been less impressive and most patients with Cushing's disease have failed to respond (78)(79)(80)(81)(82). The chronic treatment of rat pituitary tumour cells and mouse corticotroph cells with glucocorticoid results in decreased binding of somatostatin (83).…”
Section: Somatostatin Analoguesmentioning
confidence: 99%
“…The chronic treatment of rat pituitary tumour cells and mouse corticotroph cells with glucocorticoid results in decreased binding of somatostatin (83). In cultured human corticotroph, adenoma cells pre-treated with hydrocortisone resulted in abolition of octreotide-induced inhibition of basal and CRH induced ACTH release (82). The lack of clinical efficacy of octreotide may be due to the down regulation of somatostatin receptors by glucocorticoids.…”
Section: Somatostatin Analoguesmentioning
confidence: 99%
“…O hipercortisolismo reduz a expressão do SSTR2 (134) , fato que justifica a predominância de expressão de SSTR5. Dessa forma, o LRS de nova geração, com maior afinidade ao SSTR5, podem apresentar maior eficácia (135) .…”
Section: Corticotropinomasunclassified